Phytosociology of the natural regeneration of a gallery forest - Encinas, José Imaña; de Paula, José Elias (Pesquisa Agropecuaria Brasileira, 1994)
A survey of the natural regeneration of the gallery forest at the Los Macacos river (Goiás State) was carried out. Plots of 100 m2 let established the composition of the trees succession of one hectare and 2361 plants were distributed in four classes according to the height. The phytosociological value of the classes was 3,4 2,8 1,9 and 1,9 respectively, and through them it was possible to identify the phytosociological position of the species. The results of the calculation of the relative index of the natural regeneration and value of importance showed that the most important species are Cabralea cangerana Saldanha, Cheiloclinium cognatum (Mierc.) A C. Smith, Virola sebifera Aublet, Aspidosperma cylindrocarpum M.Arq., Terminalia glabrescens Mart., Xylopia emarginata Mart., Tapura amazonica Poepp. et Endl., Pouteria gardneriana Radlk, Cupania vernalis Camb. and Cardiopetalum calophyllum Schlecht.